Peering Into Candida albicans Pir Protein Function and Comparative Genomics of the Pir Family - Kim, Jisoo; Oh, Soon-Hwan; Rodriguez-Bobadilla, Rubi; Vuong, Vien M.; Hubka, Vit; Zhao, Xiaomin; Hoyer, Lois L. (Frontiers in Cellular and Infection Microbiology, 2022)
The fungal cell wall, comprised primarily of protein and polymeric carbohydrate, maintains cell structure, provides protection from the environment, and is an important antifungal drug target. Pir proteins (proteins with internal repeats) are linked to cell wall β-1,3-glucan and are best studied in Saccharomyces cerevisiae. Sequential deletion of S. cerevisiae PIR genes produces strains with increasingly notable cell wall damage. However, a true null mutant lacking all five S. cerevisiae PIR genes was never constructed. Because only two PIR genes (PIR1, PIR32) were annotated in the Candida albicans genome, the initial goal of this work was to construct a true Δpir/Δpir null strain in this species. Unexpectedly, the phenotype of the null strain was almost indistinguishable from its parent, leading to the search for other proteins with Pir function. Bioinformatic approaches revealed nine additional C. albicans proteins that share a conserved Pir functional motif (minimally DGQ). Examination of the protein sequences revealed another conserved motif (QFQFD) toward the C-terminal end of each protein. Sequence similarities and presence of the conserved motif(s) were used to identify a set of 75 proteins across 16 fungal species that are proposed here as Pir proteins. The Pir family is greatly expanded in C. albicans and C. dubliniensis compared to other species and the orthologs are known to have specialized function during chlamydospore formation. Predicted Pir structures showed a conserved core of antiparallel beta-sheets and sometimes-extensive loops that contain amino acids with the potential to form linkages to cell wall components. Pir phylogeny demonstrated emergence of specific ortholog groups among the fungal species. Variation in gene expression patterns was noted among the ortholog groups during growth in rich medium. PIR allelic variation was quite limited despite the presence of a repeated sequence in many loci. Results presented here demonstrate that the Pir family is larger than previously recognized and lead to new hypotheses to test to better understand Pir proteins and their role in the fungal cell wall.